2014
DOI: 10.1016/j.celrep.2014.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Polycomb to Pericentric Heterochromatin in Embryonic Stem Cells Reveals a Role for H2AK119u1 in PRC2 Recruitment

Abstract: SummaryThe mechanisms by which the major Polycomb group (PcG) complexes PRC1 and PRC2 are recruited to target sites in vertebrate cells are not well understood. Building on recent studies that determined a reciprocal relationship between DNA methylation and Polycomb activity, we demonstrate that, in methylation-deficient embryonic stem cells (ESCs), CpG density combined with antagonistic effects of H3K9me3 and H3K36me3 redirects PcG complexes to pericentric heterochromatin and gene-rich domains. Surprisingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
304
3
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(335 citation statements)
references
References 75 publications
26
304
3
2
Order By: Relevance
“…They extend previous studies that already suggested a role for CpG dinucleotides in PRC2 recruitment (22,23) but are also more comprehensive and provide novel mechanistic details. Interestingly, a recent study suggests that in vitro PRC2 activity is not directly inhibited by DNA methylation (38). It is thus possible that the antagonistic effect of DNA methylation on H3K27me3 deposition that we observe in vivo is dependent on additional factors, possibly the presence of methyl-CpG-binding proteins (39).…”
Section: Discussionmentioning
confidence: 60%
“…They extend previous studies that already suggested a role for CpG dinucleotides in PRC2 recruitment (22,23) but are also more comprehensive and provide novel mechanistic details. Interestingly, a recent study suggests that in vitro PRC2 activity is not directly inhibited by DNA methylation (38). It is thus possible that the antagonistic effect of DNA methylation on H3K27me3 deposition that we observe in vivo is dependent on additional factors, possibly the presence of methyl-CpG-binding proteins (39).…”
Section: Discussionmentioning
confidence: 60%
“…The fact that redistribution of H3K27me3 is deleterious in Neurospora is somewhat surprising; however, a similar observation may have been difficult to make in other experimental systems. In plants and animals, loss of heterochromatin components leads to similar redistribution of H3K27me3 (17,(58)(59)(60)(61)(62), but in these systems, depletion of H3K27me3 from Pc-target regions is sufficient to cause poor growth and developmental defects (74,75). Thus, in many organisms, it would be difficult to determine if the phenotypic defects displayed by H3K9me3-deficient strains were caused by loss of H3K27me3 from native sites or by gain of H3K27me3 in heterochromatin domains.…”
Section: Discussionmentioning
confidence: 99%
“…H3K9me3, HP1, and 5mC have all been implicated in preventing H3K27me3 redistribution to heterochromatin in animals, and reduction of 5mC leads to redistribution of H3K27me3 in plants (17,(58)(59)(60)(61)(62)71). These observations highlight the need for additional studies to fully elucidate the complex functional and regulatory relationships between heterochromatin and Pc system components.…”
Section: H2amentioning
confidence: 96%
See 1 more Smart Citation
“…Il a été établi à partir de plusieurs études montrant l'implication de PRC1 dans le recrutement de PRC2. En effet, un défaut d'expression de PRC1 entraîne une diminution de liaison de PRC2 à l'ADN, et l'adressage forcé des protéines de PRC1 à la chromatine se traduit par l'apposition de la marque H2AK119ub1 à l'origine du recrutement de PRC2 [19,20]. Des expériences de chromatographie d'affinité (ou pull down 3 ), réalisées sur des extraits nucléaires d'embryons de drosophile ou de cellules ES murines, ont révélé que les composants de PRC2 étaient, respectivement, fortement associés avec l'H2AK118ub et l'H2AK119ub.…”
Section: Synthèse Revuesunclassified